PENGARUH CAPITAL INTENSITY, PERTUMBUHAN PENJUALAN DAN INTENSITAS PERSEDIAAN TERHADAP AGRESIVITAS PAJAK - Peliaman Gulo; Tati Rosyati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of Capital Intensity, Sales Growth, and Inventory Intensity on Tax Aggressiveness. This research was conducted by analyzing the financial reports of companies in the Property and Real Estate sector listed on the Indonesia Stock Exchange for the period 2018 to 2022. The sample used in this study were 9 companies in the Property and Real Estate sector listed on the Indonesia Stock Exchange for the period 2018 to 2022 using purposive sampling technique. The data used in this study is secondary data in the form of financial reports from each company that has been sampled. The variables used in this study are Capital Intensity (X1) as the first independent variable, Sales Growth (X2) as the second independent variable, and Inventory Intensity (X3) as the third independent variable, and Tax Aggressiveness (Y) as the dependent variable. The panel data regression method is used as the research methodology in this study. The analysis of the results of this study uses the Eviews 12 Student Version Lite software. The results of this study show that the best model is the Fixed Effect Model (FEM). The results of this study show that Capital Intensity partially affects tax aggressiveness, Sales Growth partially has no effect on tax aggressiveness, and Inventory Intensity partially has no effect on tax aggressiveness. Simultaneously, Capital Intensity, Sales Growth, and Inventory Intensity affect tax aggressiveness.